Lost Voices: Central Asian Women Confronting Transition by Yvonne Corcoran-Nantes (London and New York: Zed Books, 2005. 208 pages.) (American Journal of Islam and Society, 2006)
Yvonne Corcoran-Nantes’ Lost Voices: Central Asian Women ConfrontingTransition examines how the Soviets empowered and disempowered CentralAsian women before, during, and after the communist regime. To date, thisbook is the most in-depth study of the revolutionary transformations experiencedby these women during the twentieth century. Combining her westernacademic background and sensitivity for the local context, she reachesbeyond the mainstream conceptualization of gender issues vis-à-vis theSoviet regime to examine Central Asian and western literature on gender thematicsacross disciplines, from anthropology to political science.The book opens with a sophisticated analysis of the relation betweenwestern feminist paradigms and the Soviet policy of gender equality. Bothexisted in parallel, yet were interactive. Although western feminist ideasimpacted women from the Soviet space, they represented rather marginalviews among Soviet feminists. Corcoran-Nantes explains that while theSoviet regime was empowering Central Asian women by liberating themfrom traditional religious values and setting quotas in public structures, theseradical shifts in daily life inevitably complicated their identities in varioussocial situations. The Soviet model provided some institutional frameworkfor the independence period, yet was largely inadequate in the new free marketsystem. As a result, Central Asian women faced greater problems inshaping their feminist agendas when compared to Russian women.Chapter 2 discusses why this forceful emancipation, which involvedkhujun (unveiling), replacing Islamic law with Soviet legislation, and establishingzhensovets (women councils) in the 1920-30s, was controversial. Sheargues that women were expected to follow the changes, yet still had to playimportant social roles in their families. In addition, this empowerment provokeddomestic and social violence against women. Such phenomena askhujun also engendered intra-personal conflict and hesitation among the firstgeneration of Soviet-ruled Central Asian women. Corcoran-Nantes statesthat the “emancipation of Central Asian women had far more to do with theimplementation of the Soviet political and economic project than constitutingan act of altruism” (p. 38) ...